CIPP-Based Evaluation of Guidance and Counseling Program Effectiveness at SMP S. Taman Siswa - Liana (Jurnal Pendidikan, Media, Strategi, dan Metode., 2026)
This study evaluated the effectiveness of the Guidance and Counseling program at SMP S. Taman Siswa using the CIPP model, which covers Context, Input, Process, and Product evaluation. The study employed an evaluative research design involving 40 students as questionnaire respondents and supporting informants consisting of the principal, guidance and counseling teacher, homeroom teachers, and students. Data were collected through questionnaires, interviews, observation, and documentation, then analyzed using quantitative descriptive statistics and thematic analysis. The findings showed that the overall program effectiveness was in the good category, with a mean score of 78.81. The Context component obtained a mean score of 78.25, indicating program relevance to student needs and school conditions. The Input component obtained 77.33, showing adequate support but the need to improve service instruments, counseling facilities, and documentation. The Process component obtained 79.45, indicating that orientation, information services, individual counseling, group guidance, and collaboration were implemented well. The Product component obtained the highest score, 80.20, reflecting positive impacts on student discipline, motivation, social behavior, problem-solving, and satisfaction. The study concludes that the program is effective but requires stronger needs assessment, systematic documentation, improved facilities, and measurable outcome indicators.